Design of Hole Digging Machine for Papaya Planting Preparation - Sembiring, Alexander; Wahyudi, Retno (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
The agricultural production process heavily relies on land preparation, which significantly impacts the outcomes. Optimal land preparation is the initial step towards achieving maximum yields. Digging planting holes provides suitable growth spaces, eliminates weeds, and improves soil physical properties. Currently, hole digging processes are predominantly done manually (using hoes, manual augers), which are inefficient, time-consuming, and result in uneven holes. Through this research, a machine was designed to swiftly and uniformly dig planting holes to support pepaya growth. The machine utilizes a Honda GX-120 gasoline engine with a maximum power of 2.6 kW at 3,600 rpm to drive a gearbox connected to a soil drilling shaft made of 1.25-inch-thick iron pipe with a 3.2 mm thickness and equipped with 4 mm thick iron screw blades. These machine components are integrated into a mainframe with wheels for ease of movement during the hole digging process. Proses produksi pertanian sangat bergantung pada persiapan lahan, yang akan mempengaruhi hasil yang didapatkan. Persiapan lahan yang optimal merupakan langkah awal untuk mendapatkan hasil yang maksimal. Pembuatan lubang tanam dapat menyediakan tempat tumbuh yang sesuai untuk pertumbuhan, membasmi tumbuh-tumbuhan penggangu, dan memperbaiki sifat-sifat fisik tanah. Saat ini proses pelubangan tanam masih banyak dilakukan secara tradisional (menggunakan cangkul, ulir manual) yang tidak terlalu efektif dan membuuthkan waktu yang lama untuk melakukan proses pelubangan tanam, dan menghasilkan lubang tanam yang tidak seragam. Melalui peneilitian ini dirancang sebuah mesin yang dapat membuat lubang tanam secara cepat, dan seragam yang akan mendukung proses pertumbuhan pepaya. Hasil yang dirancang menggunakan mesin penggerak motor bensin Honda GX-120 dengan daya maksimal 2,6 kW pada putaran 3.600 rpm untuk menggerakkan gearbox yang terhubung dengan poros pengebor tanah dari pipa besi berukuran 1,25 inch dengan ketebalan 3,2 mm dan terdapat daun screw besi dengan ketebalan 4 mm. Elemen-elemen mesin ini disatukan dalam sebuah rangka utama yang terdapat roda, sehingga dapat mempermudah pergerakan mesin ini dalam proses pelubangan tanam.